2020
DOI: 10.1111/jch.13853
|View full text |Cite
|
Sign up to set email alerts
|

Association between pulse pressure and aortic calcification: Findings from the National Health and Nutrition Examination Survey 2013‐2014

Abstract: Dual-energy X-ray absorptiometry (DXA) is a low-cost, minimal radiation technique commonly used to assess bone density and body composition that can also provide a measure of abdominal aortic calcification (AAC). We examined the association between pulse pressure (PP) and DXA-derived AAC in a nationally representative sample of US adults. Analyses were performed in 2,478 adults from the 2013-2014 NHANES cycle. AAC scores were calculated using a validated 24-point scale from thoraco-lumbar spine images (scored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
0
11
1
Order By: Relevance
“…For this analysis, the anterior and posterior aortic walls were separated into four segments, corresponding to the areas of the lumbar vertebrae (L1‐L4). Within each of these eight segments, aortic calcification was visually estimated with a score ranging from 0 to 24 7 . This illustrates the potential limitation in assessment of AAC and unrecognizing small calcifications that could be prevalent in general population that has been described in the present study.…”
mentioning
confidence: 75%
See 4 more Smart Citations
“…For this analysis, the anterior and posterior aortic walls were separated into four segments, corresponding to the areas of the lumbar vertebrae (L1‐L4). Within each of these eight segments, aortic calcification was visually estimated with a score ranging from 0 to 24 7 . This illustrates the potential limitation in assessment of AAC and unrecognizing small calcifications that could be prevalent in general population that has been described in the present study.…”
mentioning
confidence: 75%
“…Results regarding AAC score were different. The investigators revealed that only PP, but not SBP and DBP, was associated with AAC score in partial statistical model, but even is significance vanished after adjustment for age and antihypertensive medications 7 . There are several important points of this investigation that deserve further discussion.…”
mentioning
confidence: 85%
See 3 more Smart Citations